An EDUCATION ON MAKING NUTRIENT AGAR (NA) MEDIA FOR OBSERVING ESCHERICHIA COLI MORPHOLOGY AT IMMIM ISLAMIC BOARDING SCHOOL: EDUKASI PEMBUATAN MEDIA NUTRIENT AGAR (NA) UNTUK PENGAMATAN MORFOLOGI ESHERICHIA COLI DI SMAS PESANTREN IMMIM - Wahyuni, Sri; Kaswi, Nurwilda; Annisa, Riska; A Salim, Indra Permata; Al Adawiah, Putri Rabiah (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Service activities are carried out as an educational medium for IMMIM Islamic Boarding School students through material presentation and direct practice in making Nutrient Agar (NA) media. So, it can increase knowledge about making good media. This activity was also carried out so that students knew an in-depth explanation of the stages of making, usefulness and how important Nutrient agar media is as a growth medium and observation of the morphology of Eschericia coli bacteria. This counseling activity provided satisfaction for the participants, more than 95% of the participants strongly agreed with this activity. Community service activities have a good impact on the participants. The knowledge and understanding of IMMIM Islamic Boarding School students increased about Nutrient Agar media, the correct stages of making Nutrient Agar, the usefulness of Nutrient Agar media, and the importance of Nutrient Agar media as a growth medium and observation of the morphology of Escheria coli bacteria.